How dare you not recognize the role of my contempt? Insight from experimental psychopathology. (30th October 2017) - Grecucci, Alessandro; Frederickson, Jon; Job, Remo
Abstract: Gervais & Fessler argue that contempt is an attitude state defined as a lack of respect that potentiates the activation and deactivation of two different clusters of emotions. However, clinical and experimental findings do not support this view. We provide evidence that contempt is not an emotion, nor an attitude, but a reactive defensive mechanism evolved to help individuals avoid shame.